"You Can't Be Serious"- The Perception and Use of Humour in EFL teaching and learning in College Classroom at the University of Bahrain - Dr. Nuri R. Ageli (Abhat Journal, 2023)
The importance of using humour in college classroom cannot be underestimated for not only does it enable the teacher to teach in a relaxed atmosphere of interested students but it also means learning new language features such as vocabulary. Besides, humour is a motivating force in allaying students' fear of participating in class and asking questions. It is believed that humour in the classroom can foster mutual openness and respect and contribute to effective teaching. This paper attempts to investigate instructors' perception of humour and its use in the EFL classroom. To that end, a survey is given to 30 native and non-nativeEnglish speaking instructors in the English Language Centre as well as in the English Department at the University of Bahrain. The findings of the survey are analysed and discussed and some recommendations are made.